Mitochondrial biogenesis is required for the anchorage-independent survival and propagation of stem-like cancer cells - De Luca, Arianna; Fiorillo, Marco; Peiris-Pagès, Maria; Ozsvari, Bela; Smith, Duncan L; Sanchez-Alvarez, Rosa; Martinez-Outschoorn, Ubaldo E; Cappello, Anna Rita; Pezzi, Vincenzo; Lisanti, Michael P; Sotgia, Federica (Oncotarget, 2015)
Here, we show that new mitochondrial biogenesis is required for the anchorage independent survival and propagation of cancer stem-like cells (CSCs). More specifically, we used the drug XCT790 as an investigational tool, as it functions as a specific inhibitor of the ERRα-PGC1 signaling pathway, which governs mitochondrial biogenesis. Interestingly, our results directly demonstrate that XCT790 efficiently blocks both the survival and propagation of tumor initiating stem-like cells (TICs), using the MCF7 cell line as a model system. Mechanistically, we show that XCT790 suppresses the activity of several independent signaling pathways that are normally required for the survival of CSCs, such as Sonic hedgehog, TGFβ-SMAD, STAT3, and Wnt signaling. We also show that XCT790 markedly reduces oxidative mitochondrial metabolism (OXPHOS) and that XCT790-mediated inhibition of CSC propagation can be prevented or reversed by Acetyl-L-Carnitine (ALCAR), a mitochondrial fuel. Consistent with our findings, over-expression of ERRα significantly enhances the efficiency of mammosphere formation, which can be blocked by treatment with mitochondrial inhibitors. Similarly, mammosphere formation augmented by FOXM1, a downstream target of Wnt/β-catenin signaling, can also be blocked by treatment with three different classes of mitochondrial inhibitors (XCT790, oligomycin A, or doxycycline). In this context, our unbiased proteomics analysis reveals that FOXM1 drives the expression of >90 protein targets associated with mitochondrial biogenesis, glycolysis, the EMT and protein synthesis in MCF7 cells, processes which are characteristic of an anabolic CSC phenotype. Finally, doxycycline is an FDA-approved antibiotic, which is very well-tolerated in patients. As such, doxycycline could be re-purposed clinically as a 'safe' mitochondrial inhibitor, to target FOXM1 and mitochondrial biogenesis in CSCs, to prevent tumor recurrence and distant metastasis, thereby avoiding patient relapse.